2019
DOI: 10.1021/acs.orglett.9b00665
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Scale, Cheap, and Eco-Friendly Iron-Catalyzed Cross-Coupling between Alkyl Grignard Reagents and Alkenyl or Aryl Halides

Abstract: A new robust methodology for gram-scale iron-catalyzed cross-coupling between alkyl Grignard reagents and alkenyl or aryl halides is developed. This method does not require toxic additives such as NMP or expensive ligands. Its efficiency relies on the use of simple alkoxide magnesium salts as additives. On the basis of these results, a new procedure for one-pot synthesis of substituted benzamides from chloroesters is also proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Indeed, in the case of 5 , a nine-membered metallacycle ( 5 B R,R,R,O ) would be formed, which was found to be slightly less stable than 5 by 2.2 kcal·mol –1 (see the Supporting Information). In that case, intermolecular ligation of a tricoordinated Fe II ate species by the alkoxide moiety of an additional equivalent of 5 can occur, consistent with the beneficial effect of magnesium alkoxide salts used as additives on alkyl–alkenyl Fe-catalyzed cross-coupling, as recently reported by some of us . Intra- or intermolecular stabilization of transient iron­(II) intermediates by alkoxide moieties can thus prevent the evolution of those species toward the β-hydride elimination pathway, which can account for the good conversion of the Grignard reagent in the cross-coupling between 5 and 6a .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, in the case of 5 , a nine-membered metallacycle ( 5 B R,R,R,O ) would be formed, which was found to be slightly less stable than 5 by 2.2 kcal·mol –1 (see the Supporting Information). In that case, intermolecular ligation of a tricoordinated Fe II ate species by the alkoxide moiety of an additional equivalent of 5 can occur, consistent with the beneficial effect of magnesium alkoxide salts used as additives on alkyl–alkenyl Fe-catalyzed cross-coupling, as recently reported by some of us . Intra- or intermolecular stabilization of transient iron­(II) intermediates by alkoxide moieties can thus prevent the evolution of those species toward the β-hydride elimination pathway, which can account for the good conversion of the Grignard reagent in the cross-coupling between 5 and 6a .…”
Section: Resultssupporting
confidence: 86%
“…In that case, an intermolecular ligation of a tris-coordinated ate-Fe II species by the alkoxide moiety of an additional equivalent of 5 can occur, consistently with the beneficial effect of magnesium alkoxide salts used as additives observed on alkylalkenyl Fe-catalyzed cross-coupling, as recently reported by some of us. 17 Intra-or intermolecular stabilization of transient iron(II) intermediates by alkoxide moieties can thus prevent the evolution of those species toward β-hydride elimination pathway, which can account for the good conversion of the Grignard reagent in the cross-coupling between 5 and 6a. This result echoes a recent report by Neidig, who demonstrated that transmetallation of Grignard reagents bearing ω-acetal groups onto NHC-ligated Fe II species leads to an improved stability of the alkyliron(II) intermediates toward β-hydride elimination.…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl 4-((Phenylsulfonyl)oxy)benzoate (3q). 25 The title compound was prepared according to the general procedure using ethyl 4hydroxybenzoate 1q (33.2 mg, 0.2 mmol) and sodium benzenesulfinate 2a (49.2 mg, 0.3 mmol, 1.5 equiv), purified by column chromatography on silica gel, and eluted with petroleum ether to afford 3q (56.9 mg, 93% yield) as a pale-yellow oil. 1 H NMR (400 MHz, CDCl 3 ): δ 7.97 (d, J = 8.8 Hz, 2H), 7.83−7.81 (m, 2H), 7.67 (t, J = 7.6 Hz, 1H), 7.52 (dd, J 1 = J 2 = 7.6 Hz, 2H), 7.04 (d, J = 8.8 Hz, 2H), 4.35 (q, J = 7.2 Hz, 2H), 1.36 (t, J = 7.2 Hz, 3H); 13 C{ 1 H} NMR (100 MHz, CDCl 3 ) δ 165.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…One prominent example is the use of palladium for the selective preparation of arenes and heterocyclic scaffolds with different substitution patterns [37]. However, also non-noble transition metals like copper [38], nickel [39], and nowadays even iron [40,41,42] are firmly anchored as suitable catalysts. Besides the high chemoselectivity, a profound functional group tolerance is a main advantage of these kind of reactions.…”
Section: Still Up-to-date—halogens In Active Agentsmentioning
confidence: 99%